Increasing the service life of tank car boilers for the transportation of chemical cargoes by using the method of tread protection (Transport systems and technologies, 2024)
The article is devoted to the search for a comprehensive technical solution to increase the service life of tank car boilers by introducing an effective protection method. A significant problem of increasing the service life of tank cars for the transportation of chemicals is the high level of boiler wear, which is associated with corrosion phenomena that arise as a result of the interaction of the inner surface of the boiler with chemical corrosive cargoes. To solve the problem of the possibility of operating tank cars in terms of determining the service life due to corrosion damage, it is necessary to develop and implement comprehensive measures to assess the final service life of tank cars. At the same time, specialists, researchers and scientists face a special task - to maximize the boiler life using a progressive protection method. One of the most promising methods that can reduce the negative impact of corrosion and be applied in practice is the tread protection method. The article presents an algorithm for calculating the tread protection, which makes it possible to determine the required number of surface protection elements. The effectiveness of protection when changing the cathodic polarization is evaluated. The requirements that should determine the principles of construction of the protection system design and its functioning are considered, and a set of technical solutions and measures aimed at ensuring the protection of metal surfaces of the object of study: a tank car boiler.
Keywords: boiler; tank car; cylindrical part; shell; method of tread protection; calculation algorithm